Political influences and earnings quality: evidence from Pakistan - Muhammad Sadiq (2018)
The general objective of this study was to examine the relationship between political influences and earnings quality. Specifically, this study examined the relationship between the ruling party politically connected firms and poor earnings quality. In addition, the study also compared the opposition party politically connected firms, when politically influenced firms substitute real earnings management for accrual earnings management in Pakistan. This study used the data of 129 firms listed on the Pakistan Stock Exchange over the period 2009-2013. The Panel Corrected Standard Error (PCSE) technique was employed to solve the heteroskedasticity issue. The results showed that politically influenced firms are reporting poor earnings quality. Contrary to previous studies, politically connected firms through opposition party(s) report poor earnings quality compared to ruling party(s) politically connected firms, when earnings quality is measured by the real earnings management attribute of earnings quality. However, there is no difference between the ruling party and the opposition party political connections on earnings quality, when earnings quality is measured by the accrual earnings management attributes of earnings quality. The study also found that politically influenced firms substitute real earnings management for accrual earnings management. Further, this study revealed that firms with stronger political connections are more involved in accrual earnings management activities and firms with weaker political connections are more inclined to use the real earnings management strategy. Accordingly, regulators must keep in mind political factors during regulatory reforms. This study provides detailed investigations and deep insight on the relationship between political influences and earnings quality. This study contributes to the field of earnings management where it integrates the agency theory with the political economy theory. Apart from that, this study contributes to practice where it provides deep insight to policy- makers who are interested in improving corporate governance in Pakistan.